Differences In The Use of Diagnostic Budget and The Use of Interactive Budget: Case Study of SMEs in Palembang City - Efva Octavina Donata Gozali; Ruth Samantha Hamzah; Meita Rahmawati (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This study aims for analyzing influence styles, use budget diagnostics and interactive proxies for performance companies all at once. For comparing styles, use budget diagnostics and interactive proxies for SMEs in Palembang City. The type of data used is the primary data result of a spreading interview containing a questionnaire and alternative answers given to the respondent, which is SME managers and workers in Palembang City. Population study: there are 155,467 SMEs in Palembang City. Taking samples uses snowball sampling methods and techniques, which yield a determinant sample that yields the total sample of as many as 100 SMEs. Research data analysis techniques This is using the Software Statistical Program for Social (SPSS) version 27 with descriptive statistics and simple linear regression. Research results this show that style use budget diagnostic and interactive no influential performance company, use budget in a manner diagnostic more lots used compared to with use budget in a manner interactive.